Successful catheter ablation of a left anterior accessory pathway from the non-coronary cusp of the aortic valve. (24th September 2014) - Laranjo, Sérgio; Oliveira, Mário; Trigo, Conceição
Abstract: Left anterior accessory pathways are considered to be rare findings. Catheter ablation of accessory pathways in this location remains a challenging target, and few reports about successful ablation of these accessory pathways are available. We describe our experience regarding a case of a manifest left anterior accessory pathway ablation using radiofrequency energy at the junction of the left coronary cusp with the non-coronary cusp.